Same peculiar subset of HML1 + lymphocytes present within normal intestinal epithelium is associated with tumoral epithelium of gastrointestinal carcinomas. Issue 12 (December 1988) - Jarry, A; Cerf-Bensussan, N; Brousse, N; Guy-Grand, D; Muzeau, F; Potet, F
Abstract : The present study shows that the distribution of T lymphocytes in gastrointestinal carcinomas and their metastases mimic the distribution of T lymphocytes in normal intestine. The composition of the peritumoral reaction resembled that of normal lamina propria with a predominance of CD3 + CD4 + T cells. In contrast, lymphocytes located between carcinomatous cells showed phenotypical features similar to those of intraepithelial lymphocytes (IEL) in normal intestine; in particu(abstractlar they expressed the antigen defined by HML-1, a monoclonal antibody raised against normal human intestinal IEL which reveals 95% IEL but very few cells in lymphoid (abstractorgans and blood. As normal intestinal IEL, the majority of intratumoral lymphocytes had the CD3+ CD8+ phenotype. A panel of monoclonal antibodies and double immunostaining techniques permitted a better characterisation of minor subsets of IEL. Two subsets of HML1 + CD3 + CD4- CD8- and of HML1+ CD3- cells, representing 2% and 3% of normal intestinal IEL respectively, did not significantly increase in carcinomatous epithelium. In contrast, in carcinomatous epithelium, but not in normal intestinal epithelium, we observed the appearance of a few lymphocytes displaying the phenotype of activated T cells (CD25+) or of natural killer cells (NKHI+) or of suppressor cells (CD11+). Such cells may participate in antitumoral defence. Although a similar population of HML1+ lymphocytes is associated with normal and carcinomatous intestinal epithelium, some interactions between lymphocytes and epithelial cells may not be maintained in tumoral epithelium. It has previously been shown that HLA-DR expression by enterocytes is modulated by intraepithelial lymphocytes. In our study, no correlation could be shown between the degree of lymphocytic infiltration and the expression of HLA-DR antigens on carcinomatous cells.